TASK-TECHNOLOGY FIT AND PERSON-JOB FIT: A BEAUTY CONTEST TO IMPROVE THE SUCCESS OF INFORMATION SYSTEMS - Woro Dwi Suryani; Sumiyana Sumiyana (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This study raises the issue that information system success could be enhanced by complementing other factors. This study investigates the success of information systems by inducing2 the task-technology fit (TTF) and person-job fit (PJF) into the DeLone and McLean model. This study aims to examine, among the two induced factors, which one is able to explain and improve the success of the information systems implementation. The results of this study indicate that the TTF explains the models’ goodness of fit better than that of the PJF when induced into the modified DeLone and McLean model. This study implies this in terms of both theory and practice. Theoretically, this research presents an alternative research model that can be used to investigate the success of information systems by considering the aspect of the users’ cognitive suitability (the cognitive fit theory). Furthermore, practically, this study suggests the importance of focusing on users’ skills and competencies and, subsequently, management should do so. Additionally, the TTF recommends a simple proposition that it could be attached immediately into the individuals’ skills and competencies. However, the PJF needs to be deeply embedded in the job’s qualifications and recruitment policies.